The effect of hectorite clay on the preparation of PS-g-PAA/hectorite clay and mung bean starch superabsorbent polymer composite / Nurul Fasiha Deraman - Deraman, Nurul Fasiha (2019)
A series of novel Superabsorbent Polymer Composites (SAPCs) were prepared through emulsion polymerization technique based on partially neutralized Acrylic Acid (AA) ( AA was neutralized until PH 6 ) grafted onto polystyrene chain in the presence of mung bean starch and Hectorite clay powder as the reinforcement. In this study, N’N’-Methylenebisacrylamide (NMBA), Ammonium Persulphate and Span 60 was used as a crosslinker, initiator and dispersant respectively.